2006
DOI: 10.1021/cg050462u
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Solid-State Characterization of Nonstoichiometric Cocrystals of a Phosphodiesterase-IV Inhibitor and l-Tartaric Acid

Abstract: Evidence for a series of nonstoichiometric, isostructural, cocrystalline complexes of L-883555, a phosphodiesterase-IV inhibitor, and L-tartaric acid with stoichiometries ranging from 0.3:1 to 0.9:1 is reported here. The free base form of this compound had insufficient bioavailability and, hence, could not be developed as a candidate for safety assessment studies. Several L-tartaric acid complexes were produced during an attempted salt-formation process, with the objective of increasing the bioavailability. It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(58 citation statements)
references
References 17 publications
2
55
0
1
Order By: Relevance
“…Peaks in this IR region certainly arose from stretching of the C=O bond of the carboxylic acids [8]. Also, Variankaval et al found three important IR band regions for calibration of tartaric acid that were between 1500-850, 1801-1500 and 3000-2800 cm -1 [9].…”
Section: Fourier Transform Infrared Spectroscopy (Ftir)mentioning
confidence: 98%
“…Peaks in this IR region certainly arose from stretching of the C=O bond of the carboxylic acids [8]. Also, Variankaval et al found three important IR band regions for calibration of tartaric acid that were between 1500-850, 1801-1500 and 3000-2800 cm -1 [9].…”
Section: Fourier Transform Infrared Spectroscopy (Ftir)mentioning
confidence: 98%
“…Solvates and hydrates are typically excluded from this list. Such crystal forms could offer advantages in terms of bioavailability, 18,19 stability, and the ability to extend the product portfolio if sufficient advantages can be demonstrated by developing the cocrystal compared to the neutral form.…”
Section: Crystal Formmentioning
confidence: 99%
“…Cocrystals can significantly increase the bioavailability of poorly soluble compounds based on limited animal bioavailability studies (11)(12)(13)(14), but it should be noted that up to now, there are no human bioavailability studies available to validate the cocrystal effect on human pharmacokinetics. Some general conclusions concerning cocrystal effects on pharmacokinetics can be revealed by an analysis performed by Shan et al (10) based on animal data from 64 cocrystals involving 21 APIs, with 80% of the studied APIs from BCS class II (10).…”
Section: Introductionmentioning
confidence: 99%